Response from Mir A, Pearson S, Masood I (J Pak Med Assoc. 2023; 73: 1374-82) Where there is a will, there is a way: Enhancing contraceptive uptake in Pakistan - Ali Mir; Steve Pearson; Irfan Masood (Journal of the Pakistan Medical Association, 2023)
The introduction of the article focuses on describing the background and setting the context for the 2007-2012 Family Advancement for Life and Health project. For a more recent review of knowledge gaps in family planning in Pakistan, readers are referred to the National Institute of Population Studies (NIPS) [Pakistan] and ICF. 2019. Pakistan Demographic and Health Survey 2017-18. Islamabad, Pakistan, and Rockville, Maryland, USA: NIPS and ICF. The current Census results and the latest Pakistan Demographic and Health Survey 2017-18 data reveal that Pakistan’s fertility transition is significantly delayed compared to other countries in the region. This delay is accompanied by a high unmet need for family planning, resulting in a high incidence of unwanted pregnancies, a considerable proportion of short interpregnancy intervals, and a high maternal mortality ratio. Given these challenges, it is imperative to focus on improving access to family planning services. Continues...